POLITIK HUKUM PEMERINTAH DALAM BIDANG PERTANAHAN DARI PERSPEKTIF HAK ASASI MANUSIA - Muhammad Halwan; Almusawwir Nansa (IAIN Palopo, 2021)
This study aims to determine the legal politics of the government in the land sector from a human rights perspective. The research results were obtained through normative legal research by examining library materials or secondary data as well as legal developments that support the research. The results of this study indicate that individual property rights arise from the relationship between humans and nature, not from human-human relations. Property rights do not depend on the consent of others, but arise because of individual businesses. Property rights are natural rights that do not originate from the state, are managed individually and must be protected by the state. Land ownership rights can also be said to be human rights, not because of inherent rights to humans, but natural rights obtained from human struggles or efforts. Thus, the revocation or relinquishing of land rights from private property by force is a violation of human rights. Citizens' refusal to implement various laws and regulations in the land sector is evidence that government policies in the land sector, both at the substance or content level (het onderwerp) of the prevailing laws and regulations, have not shown serious attention to guarantee and protection of human rights.